Pandemic impact: challenges faced by entrepreneurs of logistics industry - DR GIGI G S; MS. S. SWETHA (The journal of contemporary issues in business and government, 2020)
Pandemic impact is one of the major causes that has affected and disrupted the flow of the logistics industry. Specifically during the covid-19 days, the industry had been clueless to handle tough times. The main aim of this study is to know the factors that had caused impact on the industry during the Covid times and to identify the main reason behind the struggle in shipping various products on time. Here this study involves a descriptive research method as research design and samples for the finding purpose were collected from 90 respondents along with the help of primary data. The research findings were analysed using tools like frequency analysis, mean analysis, independent t test and ANOVA analysis. It is evident that the major impact reasons were due to shortage of labour, lack of safety measures, shipment difficulties, transport isolation that made the industry to face difficult times.